Calculation and Mapping of Water Demand Balance in Pacal Bojonegoro Irrigation Area - Agung Setya Budi (NAROTAMA UNIVERSITY, Indonesia, 2021)
This research describes the problems that exist in the Pacal Bojonegoro Irrigation Area, that in the dry season farmers often experience difficulties in irrigating their fields, therefore it is necessary to calculate a balance to know how much water is short. needed during the dry season. The water balance is calculated in a theoretical way, namely by calculating using the Global Planting Plan data as water demand data, while the existing water balance uses the existing discharge data. The research location is in the Bojonegoro Regency area using rainfall data at 3 stations for 10 years, discharge data for 7 years, climatological data for the last 1 year and crop data for the last 1 year. Rainfall data is calculated to be effective rainfall data, while discharge data is calculated using the weibul formula, for climatological data it is calculated to be evapotranspiration and percolation data, while plant data is used to calculate global cropping plans. Conclusions and suggestions for use as a reference are taken from the calculation results obtained and then forwarded as input to farmers using water and the Government of the Public Works Service. SDA Bojonegoro Regency to be used as an operational evaluation of the Irrigation Network.